Crowdfunding as an Alternative Financing Model: A Comparative Study of Success Factors - Sitompul, Pretty Naomi (YUME : Journal of Management, 2024)
This study explores the key success factors influencing crowdfunding campaigns at Bank Mandiri Medan Balaikota, focusing on campaign quality, social media engagement, and backer trust. Using a quantitative approach with 60 bank customers as the sample, the research employs Smart PLS to analyze the relationships between these variables. The findings reveal that both campaign quality and social media engagement have a direct and significant impact on backer trust, which subsequently contributes to the overall success of crowdfunding campaigns. This research provides valuable insights into optimizing crowdfunding strategies and highlights the importance of trust-building in securing financial support for projects. The results offer practical recommendations for Bank Mandiri to enhance its crowdfunding initiatives and strengthen its role in alternative financing. Keywords: Crowdfunding Success, Campaign Quality, Social Media Engagement, Backer Trust